An Analysis of Factors Influencing Changes in Consumer Interest in Electric Motorcycle Purchases - Ni'mah Sinaga, Nailan; Syahbudi , Muhammad; Nurbaiti (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2024)
This study is driven by the growing concern over carbon dioxide emissions from conventional vehicles and the Indonesian government's commitment to achieving net-zero emissions by 2060, with a focus on supporting electric vehicles. In Medan, the number of electric vehicle transactions at public charging stations (SPKLU) increased by 404% in 2024, signaling a significant rise in interest in electric vehicles. The primary aim of this research is to analyze the influence of trends, price, advertising, and promotions on the purchasing interest of electric motorcycles in Medan City. A quantitative research methodology was employed, with data collected from 351 respondents through online and offline questionnaires. SPSS software was used for data analysis, which included conducting validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis. In addition, F-tests, t-tests, and coefficient of determination (R²) analysis were performed to assess the relationship between the independent variables (price, trends, advertising, and promotions) and the dependent variable (purchasing interest). The findings from hypothesis testing demonstrate that price, trends, and advertising & promotions each have a significant positive effect on the purchasing interest in electric motorcycles. Specifically, an increase in price, trends, and advertising and promotions correlates with a greater interest in purchasing electric motorcycles. The results validate the model used, confirming that these factors play a significant role in shaping consumer behavior and influencing purchasing decisions.